2018
DOI: 10.1021/acsami.8b15098
|View full text |Cite
|
Sign up to set email alerts
|

Electrical-Charge-Mediated Cancer Cell Targeting via Protein Corona-Decorated Superparamagnetic Nanoparticles in a Simulated Physiological Environment

Abstract: A critical issue in nanomedicine is on the understanding of nano−bio interface behaviors, particularly when the nanoparticles are inevitably decorated by protein coronas in the physiological fluids. In this study, the effects of particle surface corona on cancer cell targeting were investigated in simulated physiological fluids. Cell targeting was achieved by two strategies: (1) using conventional epithelial cell adhesion molecule antibody-functionalized Fe 3 O 4 nanoparticles and (2) rendering the same but na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 39 publications
2
48
0
Order By: Relevance
“…Based on FBS coated magnetic nanoparticles, the net negative charge was −49 mV when the nanoparticles were further modified by polystyrene sulfonic (PSS), leading to negligible binding to the cancer cells. (Figure C) These results indicate, on the surface of FBS modified nanoparticle, the residue of positively‐charged patches could be completely enclosed by the small molecular weight anionic polyelectrolyte.…”
Section: Electrically Charged Magnetic Nanoprobes For Circulating Tummentioning
confidence: 74%
See 1 more Smart Citation
“…Based on FBS coated magnetic nanoparticles, the net negative charge was −49 mV when the nanoparticles were further modified by polystyrene sulfonic (PSS), leading to negligible binding to the cancer cells. (Figure C) These results indicate, on the surface of FBS modified nanoparticle, the residue of positively‐charged patches could be completely enclosed by the small molecular weight anionic polyelectrolyte.…”
Section: Electrically Charged Magnetic Nanoprobes For Circulating Tummentioning
confidence: 74%
“…Several new characterization techniques have been emerging on studies of protein corona formation on nanoparticles . To investigate the effect of the nano‐surface‐decorated‐protein‐coronas on their cancer cells binding efficacy, we synthesized the positively and negatively charged magnetic nanoparticles that were treated with fetal bovine serum solution at different concentrations . Dozens of proteins in the serum were found to decorate either positive or negative surfaces of the nanoparticles, as characterized by Liquid Chromatography‐Mass Spectrometers (LC‐MS).…”
Section: Negative Cancer Cell Surface Charge and Nano Detectionmentioning
confidence: 99%
“…As already mentioned, high aspect‐ratio nanostructures are exciting targets for nanomedical investigation due to their improved biological performance and ability to enhance interactions with living cells . In particular, the ability to direct nanoparticles toward cancer cells, which typically possess more negative surface charge, using electrostatic targeting is an application deserving further investigation as a general strategy to increase the specificity of anticancer therapies 17a,24. With this in mind, we undertook preliminary testing to explore the advantageous properties of NWs comprising TerP 22 ‐Q 11 , comparing them to SMs and an uncharged nanoparticle control system (UPs), comprising PEG 22 ‐PCL 30 g TMC 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Of great interest to most researchers dealing with nanotechnology science are nanoparticles due to the fact that the most of the research works reported in the literature have focused to interconnect the engineered science of these nanomaterials with medical problems. Nanoparticles are broadly used in all areas of medicine from drug development [5][6][7] to magnetic resonance imaging and hyperthermia for the treatment of cancer [8][9][10][11], targeted drug delivery [12,13], computer tomograf (CT) and optical imaging [14,15], cellular therapy [16,17], tissue repair [18], and gene manipulations [19,20].…”
Section: Introductionmentioning
confidence: 99%